Pemanfaatan Buku Bergambar Untuk Menumbuhkan Kemampuan Berbicara Bahasa Inggris Siswa Pra Sekolah - Sri Endah Kusmartini (Politeknik Negeri Sriwijaya, 2018)
Young learner is very happy if he/she has a chance to see a book full of colorful pictures. Usually, he/she will ask many questions about the pictures and other things related with the pictures. Therefore, in this community service program, the team tried to use picture book to cultivate speaking competence of the students. The target audiences of the program were the students of SPS Sa’adatur Rahman. They were pre school students. Before the treatment was given to the students, they were asked to respond the greetings and to answer some questions about name, age, and things around them. From the test, it can be seen that they have enough vocabularies to speak simple English like good morning or this is an orange. Unfortunately, eventhough they know the vocabularies, they cannot arrange them into even very simple sentence like this is an orange. After the treatment, they were given the same test. The results showed that there were some improvements. They were able to greet their teachers and friends. They were able to say some sentences about themselves. They were also able to say some sentences about the things around them.